A Practical Study on the Survival and Development of Campus Photography Studio - Zhang, Yue; Yang, Sunwei; Liu, Jing (Journal of Education and Educational Technologies, 2023)
The 90000 mile online studio is a microcosm of many campus photography studios. It cleverly utilizes the needs of the times and political advantages to promote the development of photography industry studios on campus, while actively expanding photography studios from within and outside the school. Maintain close contact with students on campus through membership systems, social media, etc., to ensure the healthy operation of the studio on campus. Connect with society outside the campus, expand the operating scale of the studio, and ensure the sustainable and healthy development of the studio. In daily operations and management, the studio has adopted innovative systems to strengthen internal management and work coordination.